Practical radiation dosimetry across a variety of CBCT devices in Radiology. (March 2020) - Kenny, Emer; Caldwell, David; Lewis, Mandy
Highlights: Comparison of dosimetry techniques across a range of CBCT systems in Radiology. Practical issues in implementing IAEA, EFOMP and conventional techniques are described. Adoption the EFOMP protocol for open systems (C-arms) is recommended. Measurements using conventional CTDI techniques on enclosed systems (O-arm and Extremity CT) are recommended. Abstract: Cone beam technology is becoming more prominent in Radiology. In our hospital we have an extremity CT, an O-arm and a number of C-arms offering 3D capabilities. Each of these modalities use cone beam CT (CBCT) technology to image the area of interest in one single rotation. Traditional CTDI metrics for radiation dosimetry in CT depend on narrow beam geometry. The relevance of the CTDI as a dose indicator for cone beam scanning is contentious due to underestimation of dose lying outside the standard 100 mm chamber length and CTDI phantoms being of insufficient length. In an attempt to better quantify dose from cone beam scanning, alternative methodologies have been developed which attempt to counter the limitations of CTDI methodologies. In this comparison study we utilised the CBCT methodologies outlined in (i) IAEA Report 5, (ii) EFOMP's protocol on QC in CBCT and (iii) conventional CTDI measurement and tested them on various CBCT systems used in Radiology. These methods were chosen as they use equipment that is typically available to a diagnostic imaging physicist. We determine that the EFOMP protocol and the conventional CTDI method produce the best estimate of the radiation output for quality control purposes. Our conclusion is that the EFOMP protocol is the fastest and easiest method to measure a CBCT metric but it is not always accessible. For the systems in our hospital we will adopt the EFOMP protocol for open systems (C-arms) and perform CTDIVol measurements using conventional techniques on enclosed systems (O-arm and extremity CT).